Two new nematode-trapping fungi (Arthrobotrys, Orbiliaceae) from Yunnan, China - Zhang, Xin; Zhang, Fa; Jiang, Lin; Yang, Yao-Quan; Yang, Xiao-Yan; Xiao, Wen (Phytotaxa, 2022)
Arthrobotrys jindingensis and A. tongdianensis, two new species isolated from the freshwater sediment and terrestrial soil in Lanping county, Yunnan, China, are introduced based on morphology and multi-locus phylogenetic analysis (ITS, TEF and RPB2). A. jindingensis is characterized by its branched conidiophores with irregularly swollen nodular apex, pyriform or obovoid, and 1-septate conidia. A. tongdianensis is characterized by its branched conidiophores, and ellipsoid or obovate, 1-septate conidia. Phylogenetic analysis supports them as two new species within Arthrobotrys with high support. The descriptions and illustrations of these two species are provided in this paper.